Eksplorasi Hambatan dan Adaptasi Guru SD dalam Menerapkan Asesmen Diagnostik sebagai Landasan Perencanaan Pembelajaran Berdiferensiasi di SDN 2 Bakan - Dedi Sopiyan (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
The implementation of the Merdeka Curriculum in Indonesian primary schools emphasizes student-centered learning and personalized instruction, with Differentiated Learning (DL) being a core pedagogical approach. DL, which requires teachers to proactively modify content, process, product, and learning environment (Tomlinson, 2014), is fundamentally reliant on accurate and comprehensive data gathered through Diagnostic Assessment (DA). DA serves as the vital initial step, informing teachers about students’ readiness, interests, and learning profiles. However, integrating DA results—especially non-cognitive and affective data—into complex differentiated planning presents significant practical challenges for primary school teachers amidst demanding administrative and teaching loads. This review addresses the practical gap between policy requirement and classroom implementation.